Validasi Efektivitas Pamflet dalam Meningkatkan Pengetahuan dan Kesadaran Wisatawan Lokal - Hidayat, Toni (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This research aims to test the effectiveness of pamphlets through validation sheets as an information medium in increasing the knowledge and awareness of local tourists regarding existing tourist destinations. The pamphlet is designed to convey clear and engaging information about tourist attractions, facilities, and the benefits that local tourists can gain. This research is a development study using the 4D model from Thiagarajan et al. (1974) modified into 3D. The data collection technique used a validation sheet given to three expert validators competent in the fields of content/material, appearance, and language. The data analysis technique used is the percentage technique. The results of the content/material expert assessment obtained a total validation score of 26 with an average score of 86%, validation by the display expert obtained a total validation score of 28 with an average score of 70%, and validation by the language expert obtained a total validation score of 40 with an average score of 80%. The validation results from the three validators yielded a total average score of 78% with valid criteria, and the validated pamphlet was declared suitable for use without revision. Thus, the pamphlet is declared effective and suitable as a means to enhance the knowledge and awareness of local tourists, and it can be widely applied in tourism promotion efforts.